The Prognostic Value of Pretherapy Peripheral Blood Inflammatory Indices in Myelodysplastic Syndromes - Shi, Cong; Gong, Shengping; Niu, Tingting; Li, Tongyu; Wu, An; Zheng, Xiaojiao; Yang, Shujun; Ouyang, Guifang; Mu, Qitian (Frontiers in Oncology, 2022)
Background Inflammation appears to have a critical role in carcinogenesis tumor growth according to emerging research. The platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and plasma C-reactive protein (CRP) are considered to reflect the systemic inflammatory response and clinical prognosis. The prognostic value of inflammatory indices in myelodysplastic syndrome (MDS) patients remains unclear. Methods A total of 213 MDS patients were enrolled for the study. Univariate and multivariate analyses were performed to determine the prognostic significance of various indicators, including PLR, NLR, and CRP. Results MDS patients with higher PLR, NLR, and CRP levels had significantly shorter overall survival (OS). Based on univariate analysis, age (≥60 years), gender (men), lower hemoglobin level (<10 g/dl), higher bone marrow blast percentage (>5%), poorer karyotype, and higher Revised International Prognostic Scoring System (IPSS-R) score were significantly associated with shorter OS. Patients with higher CRP levels had shorter leukemia-free survival (LFS, P = 0.041). However, higher PLR and NLR had no significant influence on LFS (P > 0.05). Multivariate Cox proportional hazards regression analysis indicated that high PLR and CRP were also independent adverse prognostic factors for OS in MDS. Conclusions Elevated PLR and CRP predict poor prognosis independent of the IPSS-R and provide a novel evaluation factor for MDS patients.